Analysis of the Impact of the Omnibus Law on Society in Terms of Law Number 13 of 2003 Concerning Manpower and Law Number 11 of 2020 Concerning Work Copyright - Jefri Rahmansyah Putra; Sriono Sriono; Bernat Panjaitan (Budapest International Research and Critics University, 2021)
Government prepares Law Copyright Labor by using the concept of Omnibus Law, to be used as a scheme to build the economy in order to attract investors to invest in Indonesia. Law Number 11 of 2020 concerning Job Creation has several clusters, one of which regulates employment as stated in the previous Law, namely Law Number 13 of 2003 concerning Manpower. In the employment cluster, the Government seeks to harmonize the 3 laws so that they are in line so as to provide a space for investors to open their businesses without worrying about overlapping regulations and causing losses to investors. This research menuse normative juridical methods , the concept of the Omnibus Law So far it is not clearly regulated in Law Number 11 of 2020 concerning Job Creation . The government is trying to implement the omnibus law to create jobs. But it is not balanced with regulatory substances that are able to avoid conflicts that have occurred so far. This Job Creation Act still has many weaknesses. This problem exists in changes to the provisions for leave, giving severance pay and others. These changes further narrow the space for workers / laborers to fight for their rights.